Differential migration and activation profile of monocytes after trophoblast interaction - Grasso, Esteban Nicolas (2014)
Macrophages at the maternal-placental interface coordinate opposite demands under the control of trophoblast cells such as the response against pathogens on one hand, and apoptotic cell clearance and wound healing with the production of suppressor cytokines. Here, we investigated whether trophoblast cells induce maternal monocyte activation towards an alternative activated macrophage profile and whether bacterial or viral stimuli modulate their migratory properties. We used an in vitro model of the maternal-placental interface represented by co-cultures of CD14+ cells isolated from fertile women with first trimester trophoblast cell line (Swan-71 cells) in the presence or absence of pathogen associated molecular pattern (PAMP) stimuli lipopolysaccharide (LPS), peptidoglycan (PGN) or poly [I:C]). Maternal CD14+ cells showed increased CD16 and CD39 expression, both markers associated to an alternative activation profile, with no changes in CD80 expression after trophoblast cell interaction. These changes were accompanied by increased IL-10 and decreased IL-12 production by CD14+ cells. After stimulation with LPS, PGN or poly [I:C], monocytes co-cultured with trophoblast cells had lower production of TNF-α and IL-1β compared with non co-cultured monocytes. Interestingly, monocyte migration towards trophoblast cells was prevented in the presence of LPS or PGN but not after 24h of stimulation with poly [I:C]. LPS or PGN also decreased CCR5, CXCL-8 and CCL5 expression. Finally, trophoblast cells co-cultured with monocytes in the presence of pathological stimuli failed to increase chemokine expression, indicating a bidirectional effect. In conclusion, trophoblast might 'instruct' maternal monocytes to express an alternative activation profile and restrain their early recruitment under pathological threats as one of the first strategies to avoid potential tissue damage at the maternal-placental interface.